Health Information Systems and Management of Health Products and Technologies: A Multi-County Study on Access to Quality Affordable Health Products and Technologies - Meme, Shadrack Mururu; Kawila, Carol; Njoroge, Kezia (International Journal of Professional Practice, 2025)
Health Products and Technologies (HPTs) are critical pillars of the health system and essential to achieving Kenya’s Universal Health Coverage (UHC). UHC prioritizes access to high-quality medical care with minimal financial hardship. Despite efforts to enhance HPTs management, counties like Kisumu, Machakos, Nyeri, Kiambu, and Isiolo in Kenya face inefficiencies in the management of HPTs, leading to the unavailability of HPTs in public health facilities. This study aimed to examine the influence of health information systems on the management of Health Products and Technologies in selected Counties, Kenya. The utilization management theory guided the research, and the pragmatism paradigm supported a mixed-methods design. Quantitative data utilized a descriptive research design, while qualitative data employed an exploratory design. A census sampling method was used in the study, where 141 staff engaged in managing HPTs at level 4 and 5 public health facilities. Key informant interviews were conducted with members of the County health management team. Data collection involved pre-tested questionnaires and key informant interview guides to ensure validity and reliability. Quantitative data was analyzed using descriptive and inferential statistics, while qualitative data was thematically analyzed. The study found that the model explained 53.5 % (R Square value of 0.535) of the variance in the management of HPTs. The study revealed that health management information systems had a positive, strong, and statistically significant association with the management of HPTs (r=544**, n=106, P=0.000). The study concluded that the health management information system has a statistically significant influence on the management of HPTs in public hospitals in Kenya. The study recommends deployment and widespread adoption of HMIS across all public hospitals and the establishment of a framework that tracks the impact of HMIS on the management of HPTs.